Amino acids stimulate the endosome-to-golgi trafficking through ragulator and small GTPase Arl5 - Chen, Bing (2018)
The endosome-to-Golgi trafficking pathway is an important post-Golgi recycling route. However, there is a lack of knowledge about the regulatory mechanisms behind intracellular membrane trafficking processes in response to extracellular signals. In this study, we found that nutrient starvation reversibly caused the trans-Golgi network (TGN) membrane proteins, such as furin and CI-M6PR, translocate from the TGN to the endosomal pool. Using a series of CD8a tagged TGN membrane proteins as reporters, we demonstrated that nutrient could stimulate the endosome-to-Golgi trafficking. We found that amino acids (AAs), especially glutamine, but not growth factors or glucose, were the key factors regulating the endosome-to-Golgi trafficking in mammalian cells. Moreover, the stimulation effect of AAs on endosome-to-Golgi trafficking is probably ubiquitous, as it is observed in multiple cell lines. Thus, we made a novel discovery that the endosome-to-Golgi trafficking of cargos is inhibited and stimulated by the absence and presence, respectively, of AAs. Inspired by the mechanism of the AA-induced mTORC1 activation pathway, we hypothesized that the AA-stimulated endosome-to-Golgi trafficking pathway might share similar machinery. By selectively inhibiting or depleting each component of the AA-stimulated mTORC1 signaling pathway, it was revealed that SLC38A9, v-ATPase and Ragulator, but not Rag GTPases or mTORC1, are essential for AA-stimulated endosome-to-Golgi trafficking. To accomplish the delivery of cargos from endosomes to the Golgi, various factors, including tethering factors, SNAREs and the small GTPases from the Rab and Arf-like family, are involved. Arl5, an Arf-like family small GTPases, has been found to regulate the membrane trafficking between the endosome and the Golgi. There are three closely related paralogs of Arl5 in vertebrates – Arl5a, b and c, where Arl5a, Arl5b are the dominant ones. Endogenously and exogenously expressed Arl5a and Arl5b were found to localize in the Golgi, while human Arl5c did not display a Golgi localization. Using yeast two-hybrid, pull-down and immunoprecipitation assays, we found that Arl5 interacts with Lamtor1. Live-cell imaging revealed that Arl5b colocalizes with Lamtor1 at the endosome and lysosome. Furthermore, both Arl5 and its effector, the Golgi-associated retrograde protein complex (GARP), are required for AA-stimulated trafficking. We have therefore identified a mechanistic connection between nutrient signaling and the endosome-to-Golgi trafficking pathway, whereby SLC38A9 and v-ATPase sense AA-sufficiency. Moreover, the interaction between Lamtor1 and Arl5 might activate Arl5, which, together with its effector GARP, a tethering factor, likely facilitates the endosome-to-Golgi trafficking.